Increased Six1 expression in macrophages promotes hepatocellular carcinoma growth and invasion by regulating MMP‐9. Issue 7 (2nd May 2019) - Zhang, Yongyu; Wang, Shiji; Liu, Zhongmin; Yang, Lewei; Liu, Jian; Xiu, Ming
Abstract: Increased Six1 expression is commonly observed in a variety of cancers and is positively correlated with cancer progression and metastasis. Nevertheless, the mechanism by which Six1 affects the development of hepatocellular carcinoma (HCC) is still unclear. A series of experiments involving cell counting kit‐8, colony formation and Transwell assay was used to determine cell proliferation, migration and invasion respectively. Histological examination and immunofluorescence assay were also performed. The messenger RNA and protein expression of interesting genes were determined by real‐time reverse transcription‐polymerase chain reaction and western blotting respectively. We found that Six1 was up‐regulated in HCC and was associated with worse histological grade and poor survival rate. Increased expression of Six1 was shown to be able to boost cell growth, invasion, migration and epithelial‐mesenchymal transition (EMT), whereas silencing of Six1 suppressed these malignant phenotypes. Mechanistic investigations revealed that, in macrophages, matrix metalloproteinase 9 (MMP‐9) was up‐regulated by Six1. Interestingly, Six1 expression in macrophages was also able to trigger MMP‐9 induction in HCC cells. Moreover, macrophage Six1 expression was able to induce interleukin‐6 (IL‐6) up‐regulation and increase the activity of signal transducer and activator of transcription 3 (STAT3) in HCC cells, which accounted for the elevated levels of MMP‐9 and the higher invasive levels seen in HCC. Increased expression of Six1 in HCC aggravates the malignant behaviour of cancer cells, and we provide novel evidence that macrophage Six1 can stimulate cancer cell invasion by elevating MMP‐9 expression.